Acknowledgement of Reviewers’ Contribution - KUSOED, JER (Journal of Education and Research, 2020)
The Editorial Board and the publisher of the Journal of Education and Research would like to express their appreciation to the following colleagues for their time and effort in reviewing manuscripts submitted to the JER.